Potential Activity of Serunai Leaf Ethanol Extract (Chromolaena Odorata L.) Against the Healing of Burns - Helmidanora, Rusdiati; Wijaya, Heri; Musakir (Iraqi Journal of Pharmaceutical Sciences, 2023)
Wounds are a problem that everyone often experiences, especially burns, so they need to be addressed. In South Sulawesi, chrysanthemum leaves are believed to heal wounds. This study aimed to determine whether there was an effect of healing burns on the backs of mice by administering ethanol extract of Serunai leaves (Chromolaena odorata L.). The research conducted is experimental. The object under study is the process of healing burns on the back of male white mice. The study was conducted on 25 male white mice divided into five groups of test animals, each group consisting of 5 male white mice. The first group was given positive control (+) branded ointment, and the second group was given negative control (-) vaseline flavum, the third group was given ethanol extract of Serunai leaves with a concentration of 5%, the fourth group was given ethanol extract of Serunai leaves with a concentration of 10%. The fifth group was given ethanol extract. Serunai leaves with a concentration of 20%, and each group was replicated five times. Data were obtained from observing burns until the skin's surface on the back of the mice was covered and calculated using AUC and analyzed by the OneWay Anova test. The results showed that the ethanol extract of Serunai leaves had the potential for healing burns. Each concentration has a burn healing power of 5% (48.76%), 10% (60.34%), and 20% (67.54%) concentration.